Prediksi Kebangkrutan Menggunakan Metode Altman Z-Score Pada Perusahaan Yang Terdaftar di Bursa Efek Indonesia - Elysah Rizkiah; Adita Nafisa (Fakultas Ekonomi dan Bisnis, Universitas Islam Raden Rahmat Malang, 2023)
This study aims to predict the level of bankruptcy of companies listed on the Indonesia Stock Exchange using the Altman Z-Score method. This research uses descriptive quantitative method. The sampling method is purposive sampling as many as 14 companies. Secondary data is in the form of financial statements of companies in the plastic and packaging sub-sector for the period 2017 to 2019. The level of bankruptcy is shown through 3 zones, namely the dangerous zone, the gray area, and the healthy zone. There were 21% of plastic and packaging companies classified into the dangerous zone (bankrupt) in 2017 and 2018, increasing to 29% in 2019. There are plastic and packaging sub-sector companies classified as gray area in 2017 to 2019 at 57%. And there are plastic and packaging sub-sector companies that are classified as healthy zone categories in 2017 and 2018 by 21% and decreased in 2019 by 14%. So, it can be concluded that plastic and packaging companies experienced a stable condition in the year of the study, the increased potential for bankruptcy is due to debt greater than capital so that it will produce a minus value or in other words can bring losses to the company if debt and capital are not balanced. Strategies and suggestions for companies are to improve financial performance by conducting periodic evaluations.